2022
DOI: 10.1136/jnnp-2021-327408
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury

Abstract: ObjectiveThis study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury.MethodsWe pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated ≥7 days. Patient selection and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Within the field of non-traumatic brain injuries, especially strokes, there only exists good clinical experience as well as promising retrospective and review [ 22 , 29 , 46 ] data. Hence, there is a significant unmet need for controlled and prospective datasets within clearly defined patient collectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the field of non-traumatic brain injuries, especially strokes, there only exists good clinical experience as well as promising retrospective and review [ 22 , 29 , 46 ] data. Hence, there is a significant unmet need for controlled and prospective datasets within clearly defined patient collectives.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this assumed individual benefit it is expected that the results of this study will be of significant long-term importance to improve therapeutic standards in acute neurointensive care unit patients in general. Indeed, recently, one of the first comprehensive studies in this field [ 46 ] has shown that amantadine medication leads to an improvement of vigilance even in patients with non-traumatic brain injuries (especially those with AIS, ICH and SAH) after five days of treatment. The authors concluded that these results should be confirmed in further studies also considering the functional outcome of patients which will be part of our secondary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…We found that perturbing some receptors induced a significant shift in the dynamics of the DoC model as determined by the travelled distance as the scaling parameter increased. Of note, the least effective in terms of reaching a maximum change in the dynamics, were the dopaminergic receptors, which are currently used currently as treatment options (Giacino et al, 2012; Rühl et al, 2022). This discrepancy could arise due to downstream effects of dopaminergic stimulation not included in our model, or due to the fact that dopaminergic drugs used to treat DoC are non-specific with regards to the targeted dopamine receptor subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Zolpidem restores consciousness in chronic patients due to a paradoxical effect (Bomalaski et al, 2017), and its effect wears off along with the drug (Whyte et al, 2014;Whyte & Myers, 2009). In contrast, Amantadine is a N-methyl-D-aspartate receptor antagonist and indirect dopamine agonist capable of inducing both short (5-10 days) and long-term (4-6 weeks) improvements (Rühl et al, 2022), and it was incorporated in DoC practical guidelines for clinicians (Giacino et al, 2018). Unfortunately, available drugs have modest therapeutic efficacy and act via unknown specific mechanisms, thus hindering the development of new options, while clinical trials are difficult to organise due to low number of participants and other limitations intrinsic to patients with conscious impairments (Marino & Whyte, 2022) In recent years, serotonergic psychedelics have been proposed as a potential new treatment to accelerate the recovery of DoC patients (Scott & Carhart-Harris, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Data on demographic characteristics (age and sex), comorbidities, status on hospital admission, and intrahospital parameters were obtained, as previously published. 12 , 13 , 14 Prestroke functional status was assessed at hospital admission using the modified Rankin Scale (mRS) based on information by patients, relatives, medical records, and if applicable, caregivers and referring physicians. 15 Prestroke disability was defined as a score on the mRS of 3 or 4.…”
Section: Methodsmentioning
confidence: 99%